2022
DOI: 10.3389/fnut.2022.819980
|View full text |Cite
|
Sign up to set email alerts
|

Instant Dark Tea Alleviates Hyperlipidaemia in High-Fat Diet-Fed Rat: From Molecular Evidence to Redox Balance and Beyond

Abstract: Instant dark tea (IDT) is a new product gaining increasing attention because it is convenient and can endow significant health benefit to consumers, which is partially attributed to its high concentration of functional ingredients. However, the molecular mechanism underlying its regulatory effect on hyperlipidaemia is rarely studied. In this study, we performed omics and molecular verification in high-fat diet (HFD)-fed rat, aiming to reveal the mechanism and provide molecular evidence. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 70 publications
2
14
0
Order By: Relevance
“…It has been shown that adult females invest larger amounts of energy reserves and consume food to produce offspring ( Moyes et al, 2006 ). In this study, the abundances of Rikenellaceae_RC9_gut_group and Phascolarctobacterium were significantly higher in females than in males, promoting host nutrient absorption and health as mentioned previously ( Chen et al, 2021 ; Qin et al, 2022 ). Furthermore, the results showed that the abundances of both the phylum Verrucomicrobiota and the genus norank_o_WCHB1-41 belonging to this phylum were significantly higher in females than in males.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been shown that adult females invest larger amounts of energy reserves and consume food to produce offspring ( Moyes et al, 2006 ). In this study, the abundances of Rikenellaceae_RC9_gut_group and Phascolarctobacterium were significantly higher in females than in males, promoting host nutrient absorption and health as mentioned previously ( Chen et al, 2021 ; Qin et al, 2022 ). Furthermore, the results showed that the abundances of both the phylum Verrucomicrobiota and the genus norank_o_WCHB1-41 belonging to this phylum were significantly higher in females than in males.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, this diet structure led to the enrichment of Bacteroidota ( Zhao et al, 2019 ), which are involved in the degradation of macromolecular compounds such as proteins and carbohydrates ( Jami, White & Mizrahi, 2014 ; Hu et al, 2017 ). For example, Rikenellaceae_RC9_gut_group the dominant genera in captive individuals, is beneficial bacteria in the gut which promote host health and degradation of structural carbohydrates including lignin and cellulose ( Zened et al, 2013 ; Qin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the antioxidant genes (SOD, catalase, and GSH-Px) were decreased, while biomarkers of glucose glycolysis (Gck and Eno2) were overexpressed in high-fat-fed rats. This could be reversed by instant dark tea intervention [ 58 ]. Summarily, the new transcription factors played potential roles in the regulation of OS induced by hyperglycemia and provided evidence for further basic research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the GCK RS1799884 mutation is associated with a higher incidence of gestational diabetes mellitus (GDM) in the Chinese population ( 21 ). Its expression is also associated with hyperlipidemia, and the molecular mechanism of the regulation of hyperlipidemia by instant dark tea (IDT) has been demonstrated in rats fed with a high-fat diet and is related to the significant influence on the expression of glycoly-related genes such as GCK ( 22 ). Isoprene diphosphate isomerase (IDI) is involved in the biosynthesis of isoprene-like cholesterol, and there are two subtypes in humans, namely, IDI1 and IDI2 ( 23 ).…”
Section: Discussionmentioning
confidence: 99%